Lipid droplets and ferritin heavy chain: a devilish liaison in human cancer cell radioresistance - Tirinato, Luca; Marafioti, Maria Grazia; Pagliari, Francesca; Jansen, Jeannette; Aversa, Ilenia; Hanley, Rachel; Nisticò, Clelia; Garcia-Calderón, Daniel; Genard, Geraldine; Guerreiro, Joana Filipa; Costanzo, Francesco Saverio; Seco, Joao (eLife, 2021)
Although much progress has been made in cancer treatment, the molecular mechanisms underlying cancer radioresistance (RR) as well as the biological signatures of radioresistant cancer cells still need to be clarified. In this regard, we discovered that breast, bladder, lung, neuroglioma, and prostate 6 Gy X-ray resistant cancer cells were characterized by an increase of lipid droplet (LD) number and that the cells containing highest LDs showed the highest clonogenic potential after irradiation. Moreover, we observed that LD content was tightly connected with the iron metabolism and in particular with the presence of the ferritin heavy chain (FTH1). In fact, breast and lung cancer cells silenced for the FTH1 gene showed a reduction in the LD numbers and, by consequence, became radiosensitive. FTH1 overexpression as well as iron-chelating treatment by Deferoxamine were able to restore the LD amount and RR. Overall, these results provide evidence of a novel mechanism behind RR in which LDs and FTH1 are tightly connected to each other, a synergistic effect that might be worth deeply investigating in order to make cancer cells more radiosensitive and improve the efficacy of radiation treatments.
Gesehen am 14.02.2022